2016
DOI: 10.1099/jgv.0.000317
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral hepatitis B pseudotype entry requires sodium taurocholate co-transporting polypeptide and additional hepatocyte-specific factors

Abstract: Hepatitis B virus (HBV) is one of the world's major unconquered infections, resulting in progressive liver disease, and current treatments rarely cure infection. A limitation to discovering new therapies is our limited knowledge of HBV entry and dissemination pathways that hinders the development of in vitro culture systems. To address this gap in our understanding we optimized the genesis of infectious lentiviral pseudoparticles (HBVpps). The recent discovery that the bile salt transporter sodium taurocholate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…ISGs also restrict HCV cell-to-cell transmission (Meredith et al., 2014), consistent with our finding that NTCP contributes to HCV cell-to-cell spread (Figures 1E–1G). It should be noted that NTCP expression did not appear to affect HCV entry in a recent Huh7 cell line model (Meredith et al., 2016). Huh7.5.1 cells are derived from Huh7.5 cells, which differ from Huh7 cells by a single point mutation in the retinoic acid-inducible gene-I (Bartenschlager and Pietschmann, 2005, Zhong et al., 2005).…”
Section: Discussionmentioning
confidence: 93%
“…ISGs also restrict HCV cell-to-cell transmission (Meredith et al., 2014), consistent with our finding that NTCP contributes to HCV cell-to-cell spread (Figures 1E–1G). It should be noted that NTCP expression did not appear to affect HCV entry in a recent Huh7 cell line model (Meredith et al., 2016). Huh7.5.1 cells are derived from Huh7.5 cells, which differ from Huh7 cells by a single point mutation in the retinoic acid-inducible gene-I (Bartenschlager and Pietschmann, 2005, Zhong et al., 2005).…”
Section: Discussionmentioning
confidence: 93%
“…HepG2-NTCP K7 cells and Huh-7 NTCP cells 21,60 were cultured in Dulbecco’s Modified Eagles Medium F12 (DMEM-F12) supplemented with 10% fetal bovine serum (FBS) and penicillin/streptomycin. HepaRG cells were cultured in Williams E medium supplemented with 10% FBS, 50 U penicillin/streptomycin mL -1 , 5 μg human insulin mL -1 and 5×10 -7 M hydrocortisone hemisuccinate (Sigma).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Only human cell lines of hepatic origin reconstituted with hNTCP become HBV susceptible, and HBV replication was still restricted in NTCP‐ overexpressing non‐hepatic human HeLa cells and mouse hepatoma cell lines . In addition, human lung epithelial cells (A549) overexpressing NTCP also do not support HBV infection . These results suggested that NTCP expression alone is not sufficient to confer HBV infection and that additional liver‐specific factors are required.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In addition, human lung epithelial cells (A549) overexpressing NTCP also do not support HBV infection. 37 These results suggested that NTCP expression alone is not sufficient to confer HBV infection and that additional liver-specific factors are required.…”
Section: Hbv Infection Occurs In the Modified 293t Cells Co-culturementioning
confidence: 99%